Seismic precursors to the Whakaari 2019 phreatic eruption are transferable to other eruptions and volcanoes - Alberto Ardid; David Dempsey; Corentin Caudron; Shane Cronin (Nature Communications, 2022)
Volcanic eruptions that occur without warning can be deadly in touristic and populated areas. Using a machine learning approach, the authors here discover distinctive patterns hidden in the seismic signals of a number of New Zealand and Alaskan volcanoes, that occur before most of the eruptions studied.